ANALYSIS OF POST FEMINISM AND PATRIARKI IN SONG "THE TEASER" OF JANNETA AND MAIA ESTIANTY'S WORKS - Tita Marlina; Siti Nurjanah; Wikanengsih Wikanengsih (JLER (Journal of Language Education Research), 2020)
Since the 2000s, there have been many songs whose lyrics contain the meaning of infidelity. In line with the problem of infidelity, the development of creation and the song industry also began to highlight the problems of infidelity. One of the famous songs was titled Sang Penggoda by Tata Janneta and Maia Estianty. Women inspired many songwriters to produce works of art, which then dominated the lyrics of pop songs, dangdut, skirts, and so on. No wonder the song lyrics that describe women are selling well in the music industry market. This study analyzes the representation of postfeminism and patriarchal ideology in the song lyrics of Sang Penggoda. The research method used is critical discourse analysis with the technical analysis of Norman Fairclough's model, with the approach of postfeminism theoretical framework, patriarchal ideology, and Michael Foucault's analytical theory. The results of the study show that the song is a media forming the feminist ideology of power, namely strengthening the first woman and marginalizing the second woman. Song writers have the ability to reflect on the ideology of listeners towards post-feminism ideology and patriarchal ideology and use it to encourage oppressed women to continue to struggle to build a new image of women who are strong, firm, and independent in making decisions in their lives.